Dual-responsive multicompartment nanofibers for controlled release of payloads. Issue 49 (3rd May 2016) - Jiang, Shuai; Lv, Li-Ping; Landfester, Katharina; Crespy, Daniel
Abstract : Dual-responsive multicompartment nanofibers are designed by embedding redox-responsive nanocapsules in pH-responsive nanofibers by colloid-electrospinning and for enhanced control over the release of payloads. Abstract : Materials capable of controlling the release of functional agents are promising for drug delivery and corrosion protection. A dual-responsive multicompartment nanostructure is designed by embedding redox-responsive nanocapsules in pH-responsive nanofibers by colloid-electrospinning. This combination allows an enhanced control over the release of payloads directed by properties of nanocontainers and nanofibers.